Assessment of Gas–Particle Phase Distribution and Source Apportionment of Atmospheric Phthalate Esters and Volatile Methyl Siloxanes in Vietnamese Micro-Environments - Anh, Hoang Quoc; Hanh, Le Thi; Huong Giang, Dang Minh; Thanh Huyen, Nguyen Thi; Chau, Chu Ngoc; Hoa, Phung Duc; Minh, Tu Binh; Tri, Tran Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 1, 2020)
In this study, the gas–particle distribution characteristics and emission sources of phthalate esters (PAEs) and volatile methyl siloxanes (VMSs) were evaluated for indoor air samples collected from different micro-environments such as homes, offices, kindergartens, hair salons, laboratories, and cars in 4 cities and provinces of Hanoi, Bac Ninh, Thai Binh, and Tuyen Quang, northern Vietnam. In general, total concentrations of PAEs and VMSs were higher in gas phase as compared to particle phase; however, phase distribution profiles of individual compounds were strongly related to their structures and physicochemical properties. For examples, low-molecular-weight compounds such as dimethyl phthalate, diethyl phthalate, D3, D4, L4, and L5 were more abundant in gas phase, while heavier compounds like di(2-ethylhexyl) phthalate and L8 were preferentially associated with particle phase. Assessment of PAE emission sources is relatively difficult because they have been applied in different consumer products and materials. Significant correlation between cyclic VMSs (e.g., D4, D5, and D6) was observed, suggesting their applications in cosmetics and personal care products. Keywords: Phthalate esters, volatile methyl siloxanes, indoor air, phase distribution, source apportionment.